PEMBERDAYAAN IBU RUMAH TANGGA PADA PROGRAM ECO BUSINESS INDONESIA (EBI) DALAM MENINGKATKAN KESEJAHTERAAN (STUDI KASUS KEL. KEDAUNG KEC. PAMULANG KOTA TANGERANG SELATAN) - Gilang Tresna Putra Anugrah (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2022)
The empowerment of a community group with the aim of improving self quality so that the life and economy quality can also improve has to be done collaboratively such as using the principle of quadruple helix applied by Eco Business Indonesia. This study aims to elaborate the empowerment process that happens to the women and community of Kedaung. This study uses a descriptive qualitative method and was conducted in November 2021 to February 2022 in Kedaung village, Pamulang district, South Tangerang city. It was found that the empowerment process done by Eco Business Indonesia is in accord with what has been explained by experts; hence, provides positive impact which can be enjoyed by the program reciever and the local community so that their quality if live improves due to the enhancement of their knowledge and income.